Undergraduate students with and without mental health concerns have different perceptions of disclosing mental health challenges to instructors - J. Michael Sizemore III; Bailey Von der Mehden; Elisabeth E. Schussler (PLoS ONE, 2025)
Many undergraduates report having mental health concerns (MHC), which can reduce academic success. Students with MHC are encouraged to seek help from their instructors but may not because of perceived negative reactions by instructors and peers. This suggests stigma about MHC may differentially impact help-seeking between students with and without MHC, yet disclosure perceptions between these groups have not been investigated. This study surveyed students with and without MHC in the same classes about their hypothetical disclosure of MHC. Students in several introductory biology classes were asked whether they identified as having MHC, whether they would or would not hypothetically disclose MHC to an instructor, and why. Thematic analysis identified reasons underlying student disclosure choices, which were sorted into the three beliefs of the Theory of Planned Behavior: attitudes, subjective norms, and behavioral control. Of the 803 respondents, 50% self-identified as having MHC. Students with MHC were less likely to hypothetically disclose their MHC to an instructor than students without MHC. Students with and without MHC who said they would disclose gave similar reasons aligned with attitude beliefs. Students with MHC who said they would not disclose perceived that the instructor wouldn’t care (attitude beliefs). Students without MHC who would not disclose were concerned about keeping their MHC private (subjective norms beliefs). Students without MHC who said ‘it depends’ indicated more concerns about impact on their course performance (attitude) than students with MHC. This research found different perceptions of disclosure between students with and without MHC in these courses and suggested that students with MHC focus more on negative instructor reactions, while those without MHC focus on privacy and performance. These different perceptions may contribute to students with MHC perceiving disclosure as a negative social cost versus a positive academic benefit.